Pendidikan dan Perpaduan Nasional di Malaysia : Satu Penilaian Keberkesanan Program Sekolah Wawasan Berdasarkan Pelaksanaan di Sekolah Model - Ahmad, Ahmad Rusdi (2004)

(untitled)
National intergration is a lasting challenge for most of the multiracial of the Third World countries. Education as an institution national integration. The case of Malaysia, clearly shows that education has been mould to suit the country's need, i.e national integration, to restructing of societies and to further enhance the economy. As far as national expected by the nation builders. Until recently national integration posed a question mark, should the three ethnic interest. This study tries to show the complexities of nurturing unity among the three groups via education. The focus of this study is on the proposed Sekolah Wawasan, or Vision School, introduced by govenment in 1995, which its aim is to fostering integration among the students. The main objective of the study is to determine the effectiveness of Sekolah Wawasan in helping to achieve the aim. Since the concrete model of Sekolah Wawasan does not exist as yet, the study has to proposed Sekolah Wawasan. The school complex is located in Lurah Nilut, Bentong Pahang, which placed three primary school in one compound. The research is done in a qualitative form using the survey method and holding interviews the main technique to obtain data. It has been hypothesized that the Sekolah Wawasan could help in achieving national integration. The findings of the study comply with the hypotheses. This take place through the interaction process among the different ethnic, whereby understanding and toleration is gradually built. Although the level of integration as result of the Sekolah Wawasan is felt not only by themselves, but also by the schools' staff, parents, as well as the community as a whole. Besides integration, Sekolah Wawasan also contributes to other outcomes, as well for instance, the ability to converse in Bahasa Melayu for non-Malay study. However, there still several issues which need to be addressed, for example, regarding to the effectivness of this particular programmes in actual Sekolah Wawasan (which are under construction) especially those located in urban areas, where the possible majority of students are non-Malays. This is to fact that the study was carried out in a school in a rural area. The complex itself not actual model based on the plans as well as the concept of the programmes itself.